EU justice and home affairs law. Volume II, EU criminal law, policing, and civil law - Peers, Steve (Oxford : Oxford University Press, 2016)
A detailed examination of EU legislation and case law on immigration, asylum, visas, and border controls, this work discusses the impact and development of EU law in these complex and controversial areas.
This edition previously issued in print: 2016.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on January 5, 2017).
Keywords: Criminal law -- European Union countries; Police -- European Union countries; Civil law -- European Union countries; Law; Laws of specific jurisdictions & specific areas of law